Pengaruh lokasi terhadap serangan lalat puru Cecidochares connexa (Macquart) pada tumbuhan eksotik invasif Chromolaena odorata (L.) King & Robinson dan interaksinya dengan komunitas serangga lokal - Luna Lukvitasari; Hermanu Triwidodo; Akhmad Rizali; Damayanti Buchori (Perhimpunan Entomologi Indonesia, 2021)
The gall fly, Cecidochares connexa (Macquart) was first introduced to Indonesia to control the invasive weed Chromolaena odorata (L.) King & Robinson or kirinyuh. The purpose of this study was to determine the effect of habitat type and location, and the presence of natural enemies associated with gall flies on their level of attack. This research was be conducted in various types of habitat in Bogor and South Lampung from January to December 2019. Thirty plant samples were obtained using the area species curve method. Sampling was conducted to collect gall in each habitat, it was followed by rearing gall for ± 1 month to see insects that came out from the gall at the Biological Control Laboratory, Department of Plant Protection, Faculty of Agriculture, IPB University. The results of this study indicate that the location of the observation affects the level of attack on gall flies against kirinyuh and parachitization of gall flies by parasitoid, while the habitat does not affect both. Then there are other insects associated with kirinyuh in addition gall flies in gall, namely Lonchaea sp.